Pengaruh Ekonomi Digital Terhadap Pendapatan Industri Mikro dan Kecil di Indonesia - Sodik Dwi Purnomo; Bagus Adhitya; Zumaeroh Zumaeroh (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
This study aims to analyze the effect of digital economy, training, and partnerships on the income of micro and small industry in Indonesia. This study uses panel data from 34 provinces in Indonesia in 2017-2018. The data analysis technique used multiple linear regression with panel data approach. The results showed that the digital economy, training and partnerships have a significant positive effect on the micro and small industry in Indonesia. These findings imply 1) the need for socialization about the use of the digital economy in small and micro industry, 2) small and micro industry need to increase partnerships, and 3) the need for a training program from the government to improve the quality of products of small and micro industry in Indonesia.